Plate IV: Artist study of facial features - Salmon, William (Polygraphice, or, the Arts of Drawing, Engraving, Etching, Limning, Painting, Washing, Varnishing, Gilding, Colouring, Dying, Beautifying and Perfuming, 1685)
Engraved artist study of facial features including a side profile of the face along with details of eyes, nose, mouth, chin and ears. The most popular of William Salmon's numerous books, the title page refers to 25 plates within whereas other copies are also missing plates 3 and 10, as is the case with this particular copy. Select digitized content includes front cover, frontismatter, engraved portrait frontispiece of Salmon (age 27 in 1675), engraved title page (both by W. Sherwin) as well as recto and versos of extant copperplate engravings. Plates 22 and 23 are misbound between plates 17 and 18.
Keywords: Art metal-work; Drawing--Technique; Salmon, William, 1644-1713; Portrait painting--Technique; Beauty, Personal; Painting--Technique; Sherwin, William; Art--Early works to 1800